Shigella iron-binding proteins: An insight into molecular physiology, pathogenesis, and potential target vaccine development. Issue 30 (26th June 2022) - Hisyam Bin Ismail, Che Muhammad Khairul; Raihan Mohammad Shabani, Nor; Chuah, Candy; Hassan, Zurina; Bakar Abdul Majeed, Abu; Herng Leow, Chiuan; Kaur Banga Singh, Kirnpal; Yee Leow, Chiuan
Highlights: Iron is an essential supplement in most living organisms including the survival of the pathogens during pathogenesis. Shigella strains have evolved a variety of active uptake mechanisms to fulfill the needs of iron for survival. To compete in an iron-limited host environment, iron-binding proteins of Shigella are highly regulated for the survival. Shigella iron-binding proteins possess vital roles in physiological activity and host-pathogen interaction These proteins are potentially used for the development of therapeutic targets for the control of shigellosis. Abstract: Shigella is a well-known etiological agent responsible for intestinal infection among children, the elderly, and immunocompromised people ranging from mild to severe cases. Shigellosis remains endemic in Malaysia and yet there is no commercial vaccine available to eradicate the disease. Iron is an essential element for the survival of Shigella within the host. Hence, it is required for regulating metabolic mechanisms and virulence determinants. Alteration of iron status in the extracellular environment directly triggers the signal in enteropathogenic bacterial, providing information that they are in a hostile environment. To survive in an iron-limited environment, molecular regulation of iron-binding proteins plays a vital role in facilitating the transportation and utilization of sufficient iron sources. Given the importance of iron molecules for bacterial survival and pathogenicity, this review summarizes the physiological role of iron-binding proteins in bacterial survival and their potential use in vaccine and therapeutic developments.